Outcome Of Yoga Module As Non-Pharmacological Intervention For Chronic Low Back Pain: A Single Arm Clinical Study - Mishra, Shalinee Kumari; Mishra, Dharmendra (International Research Journal of Ayurveda & Yoga, 2021)
Introduction: Patients of Chronic Low Back Pain (CLBP) have high percentage among total low back pain cases. In Majority of cases medicinal management are in trend and in some conditions surgical care may require, but majority of CLBP can be managed through a combination of non-pharmacologic interventions such as Yoga, exercise, weight management and psychological therapies. Clinical practice guidelines for CLBP recommend physical activity (PA) as one of the most used non pharmacological interventions based on its easily applicable and low cost. Aims: Present study was undertaken to develop a Yoga Module for the management of Chronic Low Back Pain (CLBP). Materials and Methods: The study was single arm clinical study of 30 Chronic Low Back Pain patients selected randomly. Patients were administered with specific Yoga module as Non-pharmacological intervention for 2 months. Assessments of signs and symptoms before and after intervention were carried out by using Visual Analogue Scale (VAS), Stiffness Intensity Numeric Scale (SINS) and appropriately designed grading pattern (0-4) for Difficulty in Movement (DiM). Result: Statistically highly significant (p<0.0001) result in all three main symptoms; Pain (VAS), Stiffness (SINS) and Difficulty in Movement (DiM grade) were noted. Conclusion: Prepared Yoga module as non-pharmacological intervention for CLBP (Chronic low back pain) was effective up to very extent.